Evidence-Based Interventions for Children with Challenging Behavior - Armstrong, Kathleen Hague; Ogg, Julia A.; Sundman-Wheat, Ashley N.; Walsh, Audra St. John (Springer, 2014)
Challenging behavior in young children is common. It can be diffi cult for parents or early childhood professionals to know what behaviors fall within the typical range of behavior. This chapter outlines the prevalence of common behavioral concerns among young children (sleep problems, feeding issues, colic/excessive crying, toileting issues, fears/worries/anxiety, sexual behaviors, aggression, and social skills) and outlines guidelines for how to address these concerns. Strategies to ensure cultural competence in working with a diverse range of families are also outlined.
Keywords: Behavior disorders in children--Treatment; Developmental psychology